Tabungan Keluarga Sejahtera : Program Edukasi Pengelolaan Keuangan Bagi Ibu Rumah Tangga di Klambir 5 Kota Medan - Samuel Morales Simanjuntak; Astrea Wulanda; Siti Putri Luthfiyyah; Edi Zaman Berkat Gea; Yeni Absah (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
The role of financial literacy is very important in improving family welfare, especially in managing household income and expenses. Housewives, as the main manager of family finances, need a deep understanding of how to manage finances wisely. This educational program is designed to provide and improve the understanding of housewives in Klambir 5 Medan city about financial literacy. The activity methods used in this service include the presentation of financial literacy material accompanied by relevant examples, conducting interactive discussions and questions and answers to participants, and providing recommendations for financial strategies in realizing household financial welfare. Then provide assistance, and evaluate financial management practices carried out by participants in Klambir 5 Medan City in managing their household finances. The results of the program showed a significant increase in the participants' ability to manage family budgets, saving habits, and reduction of consumptive debt. The researcher also proposes a sustainable empowerment model to strengthen the impact of the program in various communities.